CONCEPTION OF CHILD: A HISTORIC REFLEXION (Fiep Bulletin - online, 2015)
This study configured as a literature revision, intended to reflect the conception of child, not from its biological genese, but in relation to epistemologic origin, or either, deepening the concept of wath comes to be the child and to understand the conceptual changes imposed in this process for the history.  Ahead of the consideration of "conception of child", it could determine the eyes with that readings of its behavior will become, of  its lacks and desires, making possible even though the accomplishment of future forecasts, not as a beginer planification of an end item, but as one better reorganization of a continued process.  From the readings, one perceived that the child concept has been modified jointly with the democratic opening of the society, and gradually the child left of being a worthless object and been considered as a singular subject of key role in the current society.
Keywords: child; concepcion; history.